Management of Costochondral Graft Overgrowth Following Treatment of Condylar Ankylosis: A Case Report - Tehranchi, Azita; Behnia, Hossein; Younessian, Farnaz; Kabiri, Sattar; Azami, Niloufar (Regeneration, Reconstruction & Restoration (Triple R), 2016)
Costochondral graft (CCG) is a common treatment modality for temporomandibular joint (TMJ) ankylosis. One of disadvantages of CCG is unpredictability of growth pattern and risk of overgrowth. This report illustrates management of a patient with CCG overgrowth. The patient was a girl, aged 7 years with severe facial asymmetry and TMJ ankylosis. The treatment comprised releasing of ankylotic mass and use of CCG for TMJ reconstruction. Four years later, the patient underwent overgrowth of the grafted side. Following clinical examination and scintigraphy, the grafted side was shaved to prevent more growth and the patient left to pass adolescent growth spurt. Ultimately, remnant deviation may be compensated by mild genioplasty and fat injection